2004
DOI: 10.1103/physrevlett.93.185002
|View full text |Cite
|
Sign up to set email alerts
|

Near-GeV-Energy Laser-Wakefield Acceleration of Self-Injected Electrons in a Centimeter-Scale Plasma Channel

Abstract: The first three-dimensional, particle-in-cell (PIC) simulations of laser-wakefield acceleration of self-injected electrons in a 0.84 cm long plasma channel are reported. The frequency evolution of the initially 50 fs (FWHM) long laser pulse by photon interaction with the wake followed by plasma dispersion enhances the wake which eventually leads to self-injection of electrons from the channel wall. This first bunch of electrons remains spatially highly localized. Its phase space rotation due to slippage with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
133
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 13 publications
8
133
3
Order By: Relevance
“…Such an energy enhancement was also observed in one of the earliest 3D PIC simulations of the laser wakefield process by Tsung et al 15 where it was observed that a second bunch of electrons was accelerated to 0.84 GeV. Hafz et al 8 26 proposed the combination of the LWFA process with the PWFA process in separate plasmas to create and then accelerate quasimonoenergetic electron bunches, carrying out PIC simulations indicating that a secondary 10 pC bunch of 500 MeV electrons could be accelerated up to 1 GeV by a 100 pC primary bunch of 500 MeV electrons.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Such an energy enhancement was also observed in one of the earliest 3D PIC simulations of the laser wakefield process by Tsung et al 15 where it was observed that a second bunch of electrons was accelerated to 0.84 GeV. Hafz et al 8 26 proposed the combination of the LWFA process with the PWFA process in separate plasmas to create and then accelerate quasimonoenergetic electron bunches, carrying out PIC simulations indicating that a secondary 10 pC bunch of 500 MeV electrons could be accelerated up to 1 GeV by a 100 pC primary bunch of 500 MeV electrons.…”
Section: Introductionmentioning
confidence: 64%
“…Finally, in the past decade, prior to which time most of the experimental accelerated electrons were characterized by an exponential energy distribution 2,3 , high quality monoenergetic electron beams were reported by many groups [4][5][6][7][8][9][10][11][12] . Most of these experiments, were conducted in the so-called blowout regime or "bubble" regime, identified in many simulations and theoretical analyses before [13][14][15][16][17][18][19][20] where the electrons are expelled radially from the beam axis by the transverse ponderomotive force of the laser, which creates a three dimensional (3D) cavity (the "bubble") empty of electrons.…”
Section: Introductionmentioning
confidence: 99%
“…15 The relativistic wake field behind intense laser pulses is periodic in one dimension 16 and shows a quasiperiodic behavior in multidimensional simulations. 17 Particle-in-cell simulations have demonstrated the generation of large-amplitude plasma wake fields by colliding laser pulses 18 or by two copropagating pulses where a long trailing pulse is modulated efficiently by the periodic plasma wake behind the first short pulse. 19 In the present paper, we consider the nonlinear interaction between two weakly relativistic crossing laser beams in plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Numerically and experimentally, the study of particle trapping and wave breaking has entered new realms with the discovery of the "bubble regime" in laser-plasma and beam-plasma interaction. 8,[16][17][18][19][20][21][22] Analytically and conceptually, however, most of the work is still confined to one dimension, and even here there is no agreement on which warm-fluid model is most suitable to describe a relativistic thermal plasma. Since 1988, there have existed two conflicting models to describe this phenomenon: one by Katsouleas and Mori, 2 and one by Rosenzweig and others.…”
Section: Admentioning
confidence: 99%